KEUNGGULAN PROVENANS ADAPTIF Eucalyptus occidentalis PADA UJI TERGENANG DAN BERGARAM - Rina Laksmi Hendrati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2012)
Waterloging and salinity in many places in the world are affected by natural conditions, geological history, irrigation practice and replacement of natural vegetations. Ground water might bring salt to soil surface at root zone areas. Engineering and vegetations are commonly used to anticipate this problem. Provisions of vegetations tolerate to this typical salty condition, although take a longer time to solve, are much cheaper and effective means to control salinity and even to rehabilitate the lands. E. occidentalis, a highly tolerant species to those conditions need to be tested as an alternative species for plantation under these conditions. Genetic materials from its natural distribution were tested to find out the most tolerant provenance under inundation and high salt level.Two controlled testings using 9 E. occidentalis provenances were conducted reaching to 300 mM salt and followed by an increased level up to sea salt concentration (550mM NaCl). Provenances from the same genetic materials were also tested in 3 field trials, i.e.: in Roberts, Sandalwindy and Kirkwood with different ranges of salt level.At salt concentration of 300mM, E. occidentalis growth was not affected, and therefore this level is too low for selection. Plants were depressed under 550mM salt and differences between provenaces are much more obvious. Different performances under high salinity were obtained from controlled condition and in field trials. Provenans Red Lake Siding and Grass Patch originated from the most extreme arid conditions nearby salty lakes showed the best ability to grow under high saline exposures on both testings.